# math

posted by .

how do you rearrange the equation 2x+y=6 and the equation -3x+4y+5=0 into standard form.

• math -

If by standard form you mean y = m x + b, where m and b are constants, then:

(1) substitute 2x from both sides of the fist equation.

(2) Add 3x - 5 to both sides of the second equation, which will give you
4y = 3x - 5 ,
and then divide both sides by 4

## Similar Questions

1. ### math/Check!

a. An ellipse is formed by stretching the graph of x^2+ y^2=1 horizontally by a factor of 3 and vertically by a factor of 4. Determine the equation of the ellipse in standard form x^2/a^2+y^2/b^2=1 (x/3) ^2+ (y/4) ^2=1 x^2/9 + y^2/16 …
2. ### someone please chek my math!

a. An ellipse is formed by stretching the graph of x^2+ y^2=1 horizontally by a factor of 3 and vertically by a factor of 4. Determine the equation of the ellipse in standard form x^2/a^2+y^2/b^2=1 (x/3) ^2+ (y/4) ^2=1 x^2/9 + y^2/16 …
3. ### Geometry HOMEWORK HELP ME PLEASE!

Draw the triangle with vertices D(-2,1), U(4,9), and E(10,1) On a Graph. 2. Find DU, UE, AND DE. (Distance) 3. Classify Triangle DUE by its sides. 4. Write the standard form of the equation of each line: DU, UE, and DE.Also, find the …
4. ### math

How do I put an equation into standard form, Ax+Bx=C?
5. ### Chemistry

How can i rearrange this Clausius-Clapeyron equation so that 1/T2 is on one side?
6. ### algebra

could you please check this answer for me and correct. thanks given equation point slope form linear equation to use to do question. y-3 = 3(x+1) question rewrite this equation in standard form y- 3 + 3 = 3x - 3x +3 + 3 -3x+ y = 6 …